The erasure of "gender" in Canadian foreign policy under the Harper Conservatives: the significance of the discursive shift from "gender equality" to "equality between women and men" - Tiessen, Rebecca; Carrier, Krystel (Canadian foreign policy journal, 2015)
An important discursive shift took place in 2009 when government staff in the Department of Foreign Affairs and International Trade (DFAIT) and the Canadian International Development Agency (CIDA) - now the Department for Foreign Affairs, Trade and Development (DFATD) - were instructed to replace the term "gender equality" with "equality between women and men". In this article, we document Canada's role as a self-proclaimed leader in the promotion of gender equality prior to 2009, and feminist critiques of Canadian foreign policy over time. We draw on feminist theory and critical foreign policy scholarship as well as interviews with mid-level bureaucrats to understand the reasons for - and implications of - the change in discourse from "gender equality" to "equality between women and men". We argue that the shift in language was significant for several reasons including a departure from Canadian best practices and Canadàs international identity in the promotion of gender equality in recent history.